3 Tesla magnetic resonance imaging in patients with cardiac electronic implantable devices: a single center experience. (3rd October 2022) - Nikorowitsch, J; Tahir, E; Erley, J; Muellerleile, K; Metzner, A; Adam, G; Blankenberg, S; Kirchhof, P; Toennis, T; Fluschnik, N
Abstract: Background: Cardiac magnetic resonance imaging (MRI), a key method guiding medical diagnosis and therapy, is increasingly performed at 3 Tesla (T) field strength. Growing evidence suggests a relatively safe conductance of 1.5 T MRI in patients with cardiac implantable electronic devices (CIEDs), leading to conditional certification of some CIEDs for MRI. However, data on the safety of MRI imaging at 3 T in patients with CIEDs are scarce. Purpose: We analysed the safety of clinically indicated 3 T MRI in patients with "3T MRI-conditional" and "3 T MRI-non-conditional" CIEDs. Methods: We performed a retrospective single-center analysis of consecutive patients with CIEDs labelled by the manufacturer as "MRI non-conditional", "1.5 T MRI-conditional" and "3 T MRI-conditional". Patients underwent clinically indicated 3 T MRI of different thoracic and non-thoracic body regions from April 2020 to February 2022. Devices were interrogated and programmed appropriately before and after scanning. Statistics included median and interquartile range. Measurements of device and lead function and integrity before and after scanning were assessed. Adverse events included all-cause death, arrhythmias, loss of capture, inappropriate anti-tachycardia therapies, electrical reset and lead or generator failure during or shortly after MRI scan. Results: One hundred twenty-eight 3 T MRI scans were performed in 94 patients (mean age 72±16 years, 36.2% female). 3T MRI scans were performed in patients with "non-MRI-conditional" devices (n=9), "1.5 T MRI-conditional" devices (n=22), and "3 T MRI-conditional" devices (n=97). Patients were pacemaker-dependent in 24 MRI scans. After MRI, lead impedance had changed by 100 Ohms or more in seven cases (4 atrial and 3 right ventricular leads). P-wave (−25%) reduction was noted in one, R-wave (−50%) reduction in two cases. Right atrial and ventricular threshold exceeded the limit of 0, 5V in one case each only in "3 T MRI-conditional" devices. No clinically relevant adverse events occurred. Conclusion: 3 T MRI was safely conducted in patients with "3 T MRI-conditional" and "non-MRI conditional" CIEDs in our single-center study. Pending verification in independent series, our data suggest that clinically indicated 3T MRI scans should not be withheld from patients with cardiac pacemakers or defibrillators. Funding Acknowledgement: Type of funding sources: None.